Virtual Reality: The World of Sexual Hyperreality - Ayuningrum, Nara Garini; Ghofar , Achmedza Aziz; Arifiana , Isrida Yul; erlinda , Nadia Aulia (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study explores the phenomenon of Virtual Reality Pornography (VR Porn) and its influence on the construction of sexuality in the digital era. Grounded in Jean Baudrillard's concept of hyperreality, the research examines how VR Porn shapes sexual preferences, expressions, and the commodification of sexuality. Utilizing a qualitative approach with a netnography method, the study analyzes user interactions and comments on the Pornhub platform to understand the dynamics of consumption and engagement with VR Porn. The findings reveal that VR Porn not only mediates virtual sexual experiences but also fosters unique expressions of intimacy, potentially altering perceptions of reality and physicality. This technology contributes to a simulated experience that feels more authentic than reality itself, shaping how users perceive and experience sexuality. Furthermore, the research highlights the dual nature of this technology—offering immersive experiences while posing risks of self-isolation, distorted intimacy, and the commodification of sexual interactions. These insights contribute to broader discussions about media technology's role in reshaping cultural and sexual paradigms, emphasizing the need for critical reflection on its social and ethical implications.